Forced Migration and the Educational Attainment of Second and Third Generations - Anica Kramer (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper studies the effects of forced migration on the educational attainment of second and third generations. Exploring the re-allocation of 8 million expellees to West Germany after World War II using German panel data, the results show that the educational outcomes of the second generation were negatively affected by the displacement of the parental generation. However, the results are driven by individuals whose both parents were expellees and by the higher end of the education distribution. The findings for third-generation expellees are, in fact, on a par with those of natives. Overall, the results of this paper imply that the social and economic costs of displacement are long lasting and go beyond the first, initially displaced generation.
Keywords: J61; O15; R23; 330; Forced migration; Economic integration; World War II; West Germany